THE RELATIONSHIP BETWEEN MEDICAL AND NON-MEDICAL STAFF INTERPERSONAL COMMUNICATION SKILLS AND OUTPATIENT PATIENT SATISFACTION AT DR. LEOKMONO HADI KUDUS REGIONAL HOSPITAL - Yesy Putri Adelia; Muhammad Purnomo; Zunia Khairunisa; Fitriana Kartikasari (PT. Radja Intercontinental Publishing, 2026)
This study is motivated by the importance of interpersonal communication between medical and non-medical staff in improving outpatient satisfaction in hospitals. The study aims to analyze the relationship between interpersonal communication skills of medical and non-medical staff and outpatient satisfaction at Dr. Loekmono Hadi Kudus Regional General Hospital. The study used a quantitative approach with an observational analytical design and a cross-sectional design. The study population was all outpatients at Dr. Loekmono Hadi Kudus Regional General Hospital with an average of 243 patient visits per day, while a sample of 152 respondents was determined using the Slovin formula with a purposive sampling technique. The research instrument used a questionnaire on interpersonal communication and patient satisfaction that had been tested for validity and reliability. Data analysis was carried out univariately and bivariately using the chi-square test. The results showed that 86.2% of respondents rated the staff's interpersonal communication skills as good and 89.5% of respondents were satisfied with outpatient services. Statistical tests showed a significant relationship between interpersonal communication skills and patient satisfaction (p = 0.001). The conclusion of this study is that good interpersonal communication contributes to increasing outpatient satisfaction in hospitals